TEM and EELS Study on TaOx-based Nanoscale Resistive Switching Devices. Issue 1805 (26th August 2015) - Norris, Kate J.; Yang, J. Joshua; Kobayashi, Nobuhiko P.
ABSTRACT: Resistive switching, a reversible change in electrical resistance of a dielectric layer through the application of a voltage bias, has propelled a field of research to form improved non-volatile memory device. Tantalum oxide has been investigated as the dielectric component of resistive switching devices as a leading candidate for a few years. Presented here is a structural and chemical investigation of TaOx devices with 55nm in diameter in the virgin, forming on, and switched off (reset) states for comparison using cross sectional TEM techniques including HRTEM, and EELS to gain further understanding of this material system. The nanodevices imaged in this study were switched below 100µA. Unique features found in this study are in agreement with previous hypotheses made by various researchers based on X-ray fluorescence microscopy of micron-scale devices, indicating a variation in oxygen concentration around the switching area.